Growing old paying for retirement and institutional money management after the financial crisis - Fuchita, Yasuyuki 1958-.; Herring, Richard; Litan, Robert E. 1950-. (Tokyo Nomura Institute of Capital Markets Research, 2011)
"Explores issues in financing retirement, from fundamental changes in types of pension plans offered to pension funds' investment strategies following the global financial crisis. Focuses in particular on the adequacy of individuals' and institutions' plans in the face of increasing life expectancy and the aging of the population"--Provided by publisher.
Introduction / Yasuyuki Fuchita, Richard Herring and Robert E. Litan -- Trends in pension system reform in East Asia: Japan, Korea, and China / Akiko Nomura -- The crisis in local government pensions in the United States / Robert Novy-Marx and Joshua Rauh -- Managing risks in defined contribution plans : what does the future hold? / Olivia S. Mitchell -- Asset allocation by institutional investors after the recent financial crisis / Robert C. Pozen, Betsy Palmer, and Natalie Shapiro.
Keywords: Pension trusts; Saving and investment; Portfolio management; Asset allocation; Financial crises -- 21st century